The role of bacterial vaginosis in infection after major gynecologic surgery. - Lin, L (1999)
PURPOSE: Previous studies have reported an association between bacterial vaginosis (BV) and postoperative fever and infection. This prospective study investigated whether the intermediate or definite stages of BV are risk factors for postoperative infection after major gynecologic surgery. METHODS: Vaginal cultures were obtained preoperatively from 175 women undergoing gynecologic surgery. The diagnostic criteria for BV were based on Nugent's standardized method of Gram stain interpretation. Postoperative fever was defined as at least one temperature equal to 101.0 degrees F or greater, or two or more temperatures more than 6 hours apart equal to 100.4 degrees F or greater. RESULTS: Thirty-six percent of the positive-BV group developed a postoperative fever, compared with 20% of the Lactobacillus-predominant group and 12% of the intermediate-BV group (P = 0.017). The differences between the positive-BV group and the Lactobacillus-predominant group, and between the positive-BV group and the intermediate-BV group, with respect to postoperative fever, were statistically significant (P = 0.045 and P = 0.007, respectively). The difference between the intermediate-BV group and the Lactobacillus-predominant group was not statistically significant (P = 0.28). CONCLUSIONS: Although the association between BV and postoperative febrile morbidity could be a spurious result of confounding with other variables, it may be prudent for the surgeon to identify patients with BV and treat them preoperatively.